A STUDY OF PRIORITY PRINCIPLE IN INDONESIAN AGRARIAN LAW SYSTEM - Winarsi, Sri; Rachmawati, Essa Adhita; Moechthar, Oemar (PEOPLE: International Journal of Social Sciences, 2020)
Land rights in agrarian law consist of two types, namely land rights for a specified period and land rights with no specific period. The community has a lack of understanding regarding land rights over a specified period, and thus, it has caused problems in the community; precisely, if the land rights have expired, the government will erase the rights and claim it as state-owned land. However, the previous landowners assumed that the existing building was their property even though the land rights had been terminated. There are a high number of disputes over ownership of land rights due to maturity. Therefore, we examine the existence of priority principles in the acquisition of land rights that have matured. The research is qualitative legal research that uses the statutory approach, conceptual approach, and case approach. Results show that the holder of land rights that have matured can be given a priority in regaining land rights, but with certain conditions set by the government.